Pengaruh Kompensasi dan Motivasi Kerja pada Tingkat Turnover Karyawan: Studi Kasus PT. B-One Jambi - Muhammad Azka Fadilyan; Hendriyaldi Hendriyaldi; Dian Mala Fithriani Aira (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This research aims to determine and analyze the effect of compensation and work motivation on employee turnover rates, with a case study conducted at PT. B-One Mineral Jambi. The study focuses on three main variables: compensation, work motivation, and employee turnover. The population of this research consists of all employees of PT. B-One Mineral Jambi, totaling 80 respondents, who were selected using a census sampling technique so that the entire population was included as the research sample. Data were collected using a structured questionnaire that had been tested for both validity and reliability to ensure the accuracy of the measurement instruments. The analytical methods used in this study included descriptive and quantitative approaches, processed with the help of the SPSS software for multiple regression analysis. The findings of this research show that compensation has a significant and positive effect on employee turnover, indicating that inadequate or unsatisfactory compensation can increase the likelihood of employees leaving the organization. Likewise, work motivation also has a significant positive effect on turnover rates, meaning that lower motivation levels tend to encourage employees to seek alternative employment. Therefore, improving compensation systems and fostering intrinsic motivation are crucial strategies to reduce turnover and maintain employee stability in the company.